If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -8x = 15 + -15x Solving 7 + -8x = 15 + -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. 7 + -8x + 15x = 15 + -15x + 15x Combine like terms: -8x + 15x = 7x 7 + 7x = 15 + -15x + 15x Combine like terms: -15x + 15x = 0 7 + 7x = 15 + 0 7 + 7x = 15 Add '-7' to each side of the equation. 7 + -7 + 7x = 15 + -7 Combine like terms: 7 + -7 = 0 0 + 7x = 15 + -7 7x = 15 + -7 Combine like terms: 15 + -7 = 8 7x = 8 Divide each side by '7'. x = 1.142857143 Simplifying x = 1.142857143
| 5-8x=35-15x | | -140-8x=10x+22 | | -35-10x=9x+32 | | 9-8x=54-43x | | 8m+6n-3m+8n= | | 4x+8=-91-7x | | 5x+8=-122-10x | | 7+5k=8k+1 | | 5x+7=-23-10x | | 6x+5=-55-9x | | 4y=2y+13 | | 5x-7+2x=63 | | (2x-1)(4x+1)= | | 122-4x=4x+18 | | -2x-8=-10 | | 110-2x=5x+19 | | 2y+11=17 | | 157-6x=5x+14 | | -3-5x=11-7x | | 3t+4=t+13 | | -45-3x=9-9x | | 2(x+2)=12 | | 113-2x=4x+23 | | 86-4x=9x+21 | | 6x-7y=47 | | 2m+5=10 | | 2x+8=80-6x | | 8+3x=29 | | (-1)(-1)(5)= | | 2x+14=49-3x | | -x-1=3x-5 | | -54-4x=6-10x |